Seeing life in the teeming world: animacy perception in arthropods - De Agrò, Massimo; Galpayage Dona, Hiruni Samadi; Vallortigara, Giorgio (Frontiers in Psychology, 2024)
The term "animacy perception" describes the ability of animals to detect cues that indicate whether a particular object in the environment is alive or not. Such skill is crucial for survival, as it allows for the rapid identification of animated agents, being them potential social partners, or dangers to avoid. The literature on animacy perception is rich, and the ability has been found to be present in a wide variety of vertebrate taxa. Many studies suggest arthropods also possess this perceptual ability, however, the term "animacy" has not often been explicitly used in the research focused on these models. Here, we review the current literature providing evidence of animacy perception in arthropods, focusing especially on studies of prey categorization, predator avoidance, and social interactions. First, we present evidence for the detection of biological motion, which involves recognizing the spatio-temporal patterns characteristic of liveliness. We also consider the congruency between shape and motion that gives rise to animacy percept, like the maintenance of a motion direction aligned with the main body axis. Next, we discuss how some arthropods use static visual cues, such as facial markings, to detect and recognize individuals. We explore the mechanisms, development, and neural basis of this face detection system, focusing on the wellstudied paper wasps. Finally, we discuss thanatosis -a behavior in which an animal feigns death to disrupt cues of liveliness -as evidence for the active manipulation of animacy perception in arthropods.